Açaí (Euterpe oleracea Mart) seed extract protects against maternal vascular dysfunction, hypertension, and fetal growth restriction in experimental preeclampsia - Alexandre de Souza da Silva; Douglas Val Quintans Nunes; Lenize Costa dos Reis Marins de Carvalho; Izabelle Barcellos Santos; Matheus Pontes de Menezes; Graziele Freitas de Bem; Cristiane Aguiar da Costa; Roberto Soares de Moura; Angela Castro Resende; Dayane Teixeira Ognibene (Taylor & Francis Group, 2020)
Objective To investigate whether Euterpe oleracea Mart. (açaí) seed extract (ASE) prevents maternal cardiovascular changes and intrauterine growth restriction (IUGR) in experimental preeclampsia (PE). Methods ASE administration (200 mg/﻿kg/day) during mid to late pregnancy in a rat model of L-NAME-induced PE. Results ASE impaired the maternal hypertension and microalbuminuria as well as the lower fetal and placental weight in experimental PE. ASE also prevented the maternal vascular dysfunction and lipoperoxidation in this model. Conclusion ASE protected against maternal cardiovascular changes and IUGR in the L-NAME-induced PE. The protective effect of ASE may be partly explained by its antioxidant property.